Hypoplasia of Left Vertebral Artery with Intimal Fibromuscular Dysplasia in a Korean Woman - Hyun, Chang Lim (The Korean Academy of Medical Sciences, 2012)
We found a case of hypoplasia of vertebral artery with fibromuscular dysplasia in an 82-yr-old Korean female cadaver during a routine dissection course. In the present case, intracranial hypoplasia in left vertebral artery and bilateral origin of posterior inferior cerebellar artery at the vertebrobasilar junction were recognized. Histopathologically, left vertebral artery showed intimal type of fibromuscular dysplasia both in its extracranial and intracranial courses. These results indicate that the association of fibromuscular dysplasia and hypoplasia does exist in the vertebral artery, although the etiologies are not verified yet.